Developing 3D-Printed Wrist Splints for Distal Radius and Scaphoid Fractures - Tobler-Ammann, Bernadette; Schuind, Frédéric; Voillat, Loïc; Gentilhomme, Théophile; Vögelin, Esther; Murith, Noé; Masserey, Bernard (Journal of Wrist Surgery, 2024)
Background The purpose of this study is to optimize conservative treatment of distal radius and scaphoid fracture, in terms of comfort, fracture stabilization, and prevention of cast complications.Description of Technique Advances in additive manufacturing have allowed the development of patient-specific anatomical braces (PSABs) which have the potential to fulfill this purpose. Our specific aims were to develop a model of PSAB, adapted to fracture care, to evaluate if this brace would be well tolerated by healthy volunteers and to determine its mechanical properties as compared with conventional methods of wrist immobilization.Materials and Methods Several three-dimensional-printed splint prototypes were designed by mechanical engineers based on surgeons' and hand therapists' clinical expertise. These experimental braces underwent testing in a preclinical study involving 10 healthy volunteers, assessing comfort, satisfaction, and activities. The final prototype was mechanically compared with a conventional cast and a prefabricated splint, testing different closing systems. A mathematical algorithm was created to automatically adapt the final PSAB model to the patient's anatomy.Results The final prototype achieved an overall satisfaction score of 79%, weighing less than 90 g, made from polyamide, and fixed using hook and loop straps. The PSAB stiffness varied between 0.64 and 0.99 Nm/degree, surpassing the performance of both conventional plaster casts and prefabricated splints.Conclusion The final wrist PSAB model, adapted for fracture treatment, is lightweight, comfortable, and provides anatomical contention. It is currently being tested for the treatment of stable distal radius and scaphoid fractures in comparison to conventional plaster cast.
Keywords: 3D printing; additive manufacturing; patient-specific anatomical brace; distal radius fracture; scaphoid fracture